2000
DOI: 10.1175/1520-0477(2000)081<2047:fiituz>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Forecast Issues in the Urban Zone: Report of the 10th Prospectus Development Team of the U.S. Weather Research Program

Abstract: The 10th Prospectus Development Team (PDT-10) of the U.S. Weather Research Program was charged with identifying research needs and opportunities related to the short-term prediction of weather and air quality in urban forecast zones. Weather has special and significant impacts on large numbers of the U.S. population who live in major urban areas. It is recognized that urban users have different weather information needs than do their rural counterparts. Further, large urban areas can impact local weather and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…(2f-h). Earlier studies in literature on sensitivity of cyclone track on land use/land cover also suggested that surface roughness and soil moisture play an important role in predicting the actual track of the cyclone [19][20][21][22][23][24][25]. This suggests that incorporation of current land use/land cover data in mesoscale model plays an important role in cyclone track prediction.…”
Section: Resultsmentioning
confidence: 99%
“…(2f-h). Earlier studies in literature on sensitivity of cyclone track on land use/land cover also suggested that surface roughness and soil moisture play an important role in predicting the actual track of the cyclone [19][20][21][22][23][24][25]. This suggests that incorporation of current land use/land cover data in mesoscale model plays an important role in cyclone track prediction.…”
Section: Resultsmentioning
confidence: 99%
“…However, the PBL is not always well defined, whenever frontal boundaries, deep convection, or multiple levels thermal inversions are involved [40]. In addition, Dabberdt et al [40] recommended the establishment of a high-resolution nation-wide observing network to monitor the diurnal variation of PBL heights.…”
Section: Planetary Boundary Layermentioning
confidence: 99%
“…In addition, Dabberdt et al [40] recommended the establishment of a high-resolution nation-wide observing network to monitor the diurnal variation of PBL heights. Their recommendation stemmed from the conclusion that Air Quality modeling accuracy is significantly limited by the lack of knowledge of the PBL structure and dynamics.…”
Section: Planetary Boundary Layermentioning
confidence: 99%
“…Further, urban growth is heterogeneous both spatially and temporally [25], and with nearly twothirds of the United States population residing in urban areas occupying less than two percent of the landmass, a detailed understanding of atmospheric processes in urban areas is critically important [26]. Not only is the awareness of impending weather changes beneficial to daily planning and emergency management for millions of urban residents, but overall public health is also impacted by local urban weather and climate.…”
Section: Introductionmentioning
confidence: 99%
“…Suite 2900, Norman, OK 73072, USA; Tel: 405-325-2541; Fax: 405-325-2550; E-mail: schroeder@ou.edu accurate forecasts, advisories, and warnings [27][28][29]. To achieve such increased levels of urban-atmospheric awareness and the growing need for general meteorological services that impact building and urban design [30], energy conservation, transport and communications, air quality and health [27,28], storm water and engineering, insurance and emergency measures [26], increased real-time researchquality observations must be collected that represent the spectrum of urban climate regions within a city [31]. However, because the urban-atmosphere interface is very complex, representative measurements are often difficult to collect [32].…”
Section: Introductionmentioning
confidence: 99%